Health literacy and its association with antibiotic use and knowledge of antibiotic among Egyptian population: cross sectional study - Sally Waheed Elkhadry; Marwa Ali Haseeb Tahoon (BMC, 2024)
Abstract Background High prevalence of inappropriate antibiotic use in different sectors of the community indicates a possible strong influence of social and cultural context, which may be influenced by social determinants of health and thereby affecting individuals' health-related behavior, including antibiotic use. And such health-related behavior is largely determined by individuals' health literacy. Objective The purpose of this research was to examine the relationship between the Egyptian population's health literacy, antibiotic use, and antibiotic knowledge. Method In Egypt, researchers used a cross-sectional study design, between the period of January and March 2024 using validated questionnaires and recruited a convenient sample of adults from seven governorates representing different geographic areas, and socioeconomic and educational backgrounds with the help of the validated questionnaires the HLS-EU-Q16, a shortened version of the European Health Literacy Survey Questionnaire (derived from the World Health Organization's Antibiotic Resistance: Multi-Country Public Awareness Survey) and, familiarity with drugs and understanding of antibiotic resistance via online methods and face-to-face interviews. Results The survey included a participation of 500 persons in total. The participants' age distribution indicated that 28.8% (n = 144) were aged 18-24, while 27.4% (n = 137) were within the 25-34 age group. Moreover, a total of 274 participants, accounting for 54.8% of the sample, described themselves as female. Significantly, 60.7% of the patients indicated acquiring antibiotics without a prescription. The evaluation of health literacy (HL) levels among the participants revealed that 36.2% had problematic HL, while 8.4% showed inadequate HL. A strong positive link was found between the scores of antibiotic knowledge and the scores of HL (R = 0.876; P-value = 0.001). Conclusion Overall, it is imperative to implement awareness-raising curricula and public health education initiatives without delay. Furthermore, it is highly advised to implement public health awareness initiatives about the appropriate use of antibiotics, alongside national policies aimed at regulating the availability and prescription of antibiotics.